Towards Sdg 12: optimizing stakeholder engagement for sustainable development - Carvalho, Victoria Sant´ Anna Feres de (2024)
The emerging global focus on sustainable development, brings attention for collective action. This thesis qualitatively explores stakeholder engagement's role in achieving SDG 12, mainly in regards to consumer involvement. Through questioning and exploring what brings up sustainable awareness to individuals, this thesis aims to understand how sustainable development can be fostered in a collective way. In this sense, the study lights up for catalytic actions towards sustainable development, encouraging critical reflection, dialogue and collaboration.